Functional Analysis of the C-5 Sterol Desaturase PcErg3 in the Sterol Auxotrophic Oomycete Pathogen Phytophthora capsici - Wang, Weizhen; Cui, Tongshan; Zhang, Fan; Xue, Zhaolin; Zhang, Borui; Liu, Xili (Frontiers in Microbiology, 2022)
Although sterols play an important role in most eukaryotes, some oomycetes, including Phytophthora spp., have lost the sterol synthesis pathway. Nevertheless, the ERG3 gene encoding C-5 sterol desaturase in the sterol synthesis pathway is still present in the genomes of Phytophthora spp. Phytophthora capsici, a destructive pathogen with a broad range of plant hosts, poses a significant threat to the production of agriculture. This study focused on the ERG3 gene in P. capsici (PcERG3) and explored its function in this pathogen. It showed that the PcERG3 gene could be expressed in all tested developmental stages of P. capsici, with sporangium and mycelium displaying higher expression levels. A potential substrate of Erg3 (stellasterol) was used to treat the P. capsici wild-type strain and a PcERG3Δ transformant, and their sterol profiles were determined by GC-MS. The wild-type strain could convert stellasterol into the down-stream product while the transformant could not, indicating that PcErg3 retains C-5 sterol desaturase activity. By comparing the biological characteristics of different strains, it was found that PcERG3 is not important for the development of P. capsici. The pathogenicity of the PcERG3Δ transformants and the wild-type strain was comparable, suggesting that PcERG3 is not necessary for the interaction between P. capsici and its hosts. Further investigations revealed that the PcERG3Δ transformants and the wild-type strain displayed a similar level of tolerance to external adversities such as unsuitable temperatures, high osmotic pressures, and intemperate pH, signifying that PcERG3 is not essential for P. capsici to cope with these environmental stresses.